Gender Justice in Religious Court Rulings: A Study of Women as The Main Breadwinners - Hutagalung, Syahrial Arif; Purba, Agnestya Yolanda; Naldo, Jufri; Nasution, Batara Abdullah; Ismail, Ismail; Hanif, Maulana Akhyar (Universitas Islam Negeri Sumatera Utara, 2025)
Social and economic transformations are prompting an increasing number of women to assume the position of primary earners within the household. Despite its integration into contemporary social realities, this phenomena presents legal issues within the framework of Islamic family law and religious court traditions, particularly regarding the delineation of duties, rights, and obligations within the household. This study seeks to examine the legal implications of Religious Courts about women as the economic foundation of the family, and to assess the degree to which the principle of gender justice is implemented in matters of maintenance, divorce, and child custody. The employed methodology is qualitative, utilising a juridical-empirical approach, involving an analysis of pertinent Religious Court rulings and interviews with judges and individuals possessing firsthand experience with the matter. The research findings indicate a lack of consistency in the implementation of gender justice principles, wherein women's economic contributions frequently lack commensurate recognition and legal protection, particularly regarding post-divorce maintenance and the allocation of caregiving responsibilities. These findings necessitate a rethinking of Islamic legal principles that is more responsive to contemporary social realities, including reforms in religious court policies that are more inclusive and gender-sensitive to secure substantive justice for women as major breadwinners.